Genotypic and phenotypic spectrum of VWF exon 20 variants in type 1 Von Willebrand disease: Insights from Eastern Saudi Arabia - Alzahrani, Faisal M.; Al Faris, Asma A.; Shaikh, Saeed Sattar; Bashawri, Layla A.; Hassan, Fathelrahman Mahdi; Aldossary, Maryam A.; Sultan , Osama Al; Al-Maqati, Thekra N.; Elnagi, Elmoeiz A.; Alqahtani, Faten Abdullah; Adam, Ahmed Adlan Mohammed; Alsuhaibani , Omar; et al. (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: VWD is a genetic bleeding disorder, divided into three types VWD types 1,2, and 3. Aim was to determine whether a common SNP present at exon 20 of the VWD gene is associated with ABO groups, VWF levels, and platelet aggregation-related functional consequences in the Eastern Saudi Arabia. Methods: It included 160 cases and controls, 60 of whom were cases from 19 families, all participants were categorized into four groups: 22 index cases who had previously been diagnosed with type 1 VWD, 21 family members who had also been diagnosed with type 1 VWD, 17 unaffected family members, and 100 healthy Saudi controls. Results: The results indicate that the distribution of blood groups among different study groups was statistically significant. It also indicates that the VWF: Ag, VWF: RCO assay, VWF: RCO/ VWF: Ag ratio and FVIII: C are significantly lower in index cases and affected family members than in non-affected family members and control groups. Among the 60 DNA samples, one variant (c.2555A>G) was found in all 60 samples, with 83.3% homozygous and 16.6% heterozygous. Conclusions: It appears that VWF levels are influenced by blood groups. One variant identified in exon 20 with a high prevalence in our population does not appear to be associated with disease status or may act in conjunction with other factors, so, further comprehensive genomic analyses of VWF are recommended to gain a better understanding of disease.